Portrait of the figure of Buya Hamka in the film Buya Hamka Vol.1 (A Semiotic Study) - Hermawan, Elpa (Jurnal Dakwah dan Komunikasi, 2024)
Photographing a character's life journey into an interesting film is a job full of challenges. The accuracy of the narrative, setting, and the ability to bring back the characters is a process that is not easy. Buya Hamka Film Vol. 1 itself cannot be separated from criticism and public scrutiny, such as a hanging story and less than optimal supporting cast. But on the other hand, many people also appreciate the story and actors in this film. Apart from that, discussions about how long it took to make the film also filled social media timelines a few days after the film was released. Therefore, this research aims to look at the figure of Hamka depicted in the film using a semiotic perspective. This research uses Roland Barthes' semiotic analysis as a reference in dissecting symbols in films. Data collection was carried out by watching films repeatedly, then recording scenes and conversations which could be used as data to then be analyzed semiotically. The research results show that the film Buya Hamka Vol. Figure 1 shows symbols and dialogue depicting the figure of Hamka. The portrait of Hamka in this film includes his ability to preach through writing, a humanist and simple figure, as well as a political figure. It is hoped that further research can dissect this film with other approaches and methods to see another side of this work.